2018
DOI: 10.1016/j.euroecorev.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the heterogeneous effects of ECB unconventional monetary policies across euro area countries

Abstract: The Working Paper Series seeks to disseminate original research in economics and fi nance. All papers have been anonymously refereed. By publishing these papers, the Banco de España aims to contribute to economic analysis and, in particular, to knowledge of the Spanish economy and its international environment. The opinions and analyses in the Working Paper Series are the responsibility of the authors and, therefore, do not necessarily coincide with those of the Banco de España or the Eurosystem. The Banco de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(53 citation statements)
references
References 19 publications
3
42
0
1
Order By: Relevance
“…This suggests that policy measures that have been successful in this regard will have a substantially positive effect on output, although they were more so in the core. This result is consistent with the finding in Burriel and Galesi (2016). However, the incremental effect on output would be even larger.…”
Section: Effects Of Unconventional Policiessupporting
confidence: 83%
See 1 more Smart Citation
“…This suggests that policy measures that have been successful in this regard will have a substantially positive effect on output, although they were more so in the core. This result is consistent with the finding in Burriel and Galesi (2016). However, the incremental effect on output would be even larger.…”
Section: Effects Of Unconventional Policiessupporting
confidence: 83%
“…This is a more agnostic scheme than that of Burriel and Galesi (2016), or other papers, which impose certain effects for these monetary policy variables, but in line for instance with Ciccarelli et al (2013). To the extent that our purpose is to understand the effect of monetary policy, we prefer to keep the shock identification procedure as agnostic as possible.…”
Section: Specification Of the Modelmentioning
confidence: 99%
“…10(d) that the cross-sectional dependence of the country residuals is generally weak. The cumulative density function of the pairwise correlations across the country residuals show that 90% of the mass lies below 30%, indicating weak cross-sectional dependence (Burriel and Galesi, 2018).…”
Section: A3 Convergence Properties Of the Markov Chain Monte Carlo mentioning
confidence: 99%
“…However, even though the effects over output were quantitatively similar to an interest rate shock, in the case of level prices they were softer and less persistent. Additionally, Burriel and Galesi (2018) analysed heterogeneity across member states and showed that unconventional monetary measures had a higher effect, especially in terms of output impact, in countries with more robust banking systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, a growing literature is focused on assessing the effectiveness of the ECB's unconventional monetary actions, covering topics ranging from the impact on sovereign bond interest to the impact on expectations and investor sentiment. Creel, Hubert, and Viennot (2016), Horvath, Kotlebova, and Siranova (2018), Eser and Schwaab (2016) and Jäger and Grigoriadis (2017) studied the effects on interest rate channel, both in terms of monetary markets and sovereign bond yields; Gambacorta, Hofmann, and Peersman (2014), Boeckx, Dossche, and Peersman (2017), Gambetti and Musso (2017), Burriel and Galesi (2018) and Conti, Neri, and Nobili (2017) focused on the impact of the ECB's unconventional policy on economic activity and prices evolution. Even Galariotis, Makrichoriti, and Spyrou (2018) and Lutz (2015) assessed the role that unconventional monetary policy played in expectations and investor sentiment.…”
mentioning
confidence: 99%